Investigating level of understanding and compliance of written work procedures to reduce occupational harm at MMHE - Mahinder Singh, Santokh Singh; Sarjit Singh, Manvender Kaur; Shamsudin, Sarimah (American Scientific Publishers, 2015)
Over the last six years (2007 to 2013) Malaysian Marine and Heavy Engineering (MMHE) has recorded four fatality cases, 36 cases of Lost Time Incident (LTI), 24,964 lost work days, 24 Restricted Work Case, 28 Medical Treatment Case, 83 First Aid cases with recorded 196,352,113 man hours worked.On average, it has approximately 29 workers sustaining occupational harm annually. This paper reports the findings of a survey conducted using a set of questionnaire, in order to identify the main causes of occupational harm occurring in MMHE.Data was gathered using 150 workers from various different work stations in the company.The findings indicated that the main causes of occupational harms were the workers (70% foreigners (from 7 nations) and 30% locals) were not following or understanding the written work procedures and the work procedures were not being enforced by managers or superiors. The findings were used to justify the need of research into investigating the effectiveness of written workplace procedures and to reduce workplace occupational harms.